Assessing ecological performance thresholds in fire‐prone Kakadu National Park, northern Australia. Issue 7 (7th July 2017) - Russell‐Smith, Jeremy; Evans, Jay; Edwards, Andrew C.; Simms, Anthony
Abstract: Contemporary fire regimes are recognized as a key threatening process for relatively immobile vertebrates and narrowly dispersing obligate seeder plant taxa in fire‐prone Australian savannas. Here, we assess the efficacy of proposed ecological performance threshold metrics for evaluating the current state of fire management for biodiversity conservation outcomes in Australia's premier, and best publicly funded savanna reserve, Kakadu National Park. The assessment draws on available data describing Landsat‐scale fire mapping over the period 1997–2015, habitat mapping, and mostly modeled responses of vegetation and faunal attributes. Despite conceptual and technical issues associated with various proposed performance thresholds and mapping products, the assessment demonstrates significant challenges with the current state of the reserve's fire management program. For example, by the end of 2015 it was observed that just 6% of woodland habitat in lowland and 23% in upland situations had remained unburnt for longer than three years and 98% of mapped fires in lowland and 87% in upland habitats were >1 km 2 in extent. Of 14 assessed performance threshold metrics, two were within acceptable thresholds at the end of 2015, and none had improved materially over the decadal assessment period. Given substantial resources evidently required to deliver effective, seasonally intensive, fine‐grained adaptive fire management for biodiversity conservation outcomes in fire‐prone Australian savannas, we suggest that alternative resourcing opportunities through market‐based savanna burning greenhouse gas emissions abatement projects need to be explored.